THE INFLUENCE OF FINANCIAL PERFORMANCE, LIFESTYLE, AND GOVERNMENT SUPPORT ON THE SMEs BEHAVIOR IN USING P2P LENDING - Adawiah, Arabiatul; Sawile, Rusnawati; MS, Eka Indriyani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Since 2013 until Indonesia has passed the covid transition period, the evolutionary development of information and communication technology (ICT) has changed SMEs lifestyles and business activities to simple, fast-response, and efficient information technology-based financial services known as fintech. Two fintech popular in Indonesia, it’s mobile payment and P2P lending. This study analyzes the influence of financial performance, lifestyle, and government support on the SMEs behavior in using P2P lending in South Sulawesi. This is quantitative research by collecting data through questionnaires distributed to respondents. This study uses a structural equation model with Smart-PLS 4.0 software. By referring to the Hair formula which is 13 x 10 indicators, the target sample in this study was 130 SMEs. But when distributing the questionnaire the number of respondents who filled out the questionnaire there were 176 respondents, so in this study the amount of data processed was 176 respondents. The result shows that financial performance and lifestyle significantly affect the SMEs behavior. While, government support does not significantly affect the SMEs behavior.